2016
DOI: 10.3109/0886022x.2016.1148557
|View full text |Cite
|
Sign up to set email alerts
|

The role of vitamin D receptor gene polymorphisms in Turkish infants with urolithiasis

Abstract: Polymorphisms in the vitamin D receptor (VDR) gene have recently been reported to be associated with urinary calculi in pediatric and adult cases, but no studies have looked at the youngest period of life. The purpose of this study was to investigate the role of VDR gene polymorphisms in infantile urolithiasis in a Turkish population. We compared a study group of 104 infants (55 girls and 49 boys, mean age 6.94 ± 3.81 months) with a control group of 96 infants (51 girls and 45 boys, mean age 7.51 ± 3.23) to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…As shown in Figure , 17 studies were included in this research . In contrast with the previous research, 13 articles were excluded due to they do not meet the HWE. The primary characteristics of the 17 studies are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure , 17 studies were included in this research . In contrast with the previous research, 13 articles were excluded due to they do not meet the HWE. The primary characteristics of the 17 studies are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1, 17 studies were included in this research (11,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). In contrast with the previous research, 13 articles (10,12,14,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) were excluded due to they do not meet the HWE. The primary characteristics of the 17 studies are summarized in Table 1.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The roles of VDR polymorphisms were also investigated in urolithiasis and nephrolithiasis. Goknar et al demonstrated that the BsmI and TaqI VDR genotypes may be candidate genes causing infantile urolithiasis [ 35 ]. But another study showed that none of the VDR ApaI, BsmI, and TaqI polymorphisms created any significant risk for urolithiasis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 31 articles (Jackman et al, 1999;Ruggiero et al, 1999;Chen et al, 2001a,b;Nishijima et al, 2002;Ozkaya et al, 2003;Shaogang et al, 2003;Relan et al, 2004;Rendina et al, 2004;Shao-Qun et al, 2004;Bid et al, 2005a,b;Gunes et al, 2006;Liu et al, 2007;Moyano et al, 2007;Seyhan et al, 2007;Wang et al, 2009Wang et al, , 2012Li Zhengming and Shi, 2010;Mittal et al, 2010;Mossetti et al, 2010;Seo et al, 2010;Aji et al, 2012;Basiri et al, 2012;Ruan et al, 2012;Guha et al, 2015;Aykan et al, 2016;Cakir et al, 2016;Goknar et al, 2016;Subaşi et al, 2017;Huang et al, 2019) reporting the relationship between VDR ApaI, BsmI, FokI, or TaqI gene variants and urolithiasis susceptibility were recruited through the search strategy (Figure 1 and Table 2). The data we needed were extracted fully ( Table 2).…”
Section: Features Of Recruited Studiesmentioning
confidence: 99%